Long-term telemonitoring of mobility trends of elderly people using SMS messaging. - Scanaill, C.N (IEEE Transactions on information technology in biomedicine)
A telemonitoring system, based on short message service (SMS), has been developed to remotely monitor the long-term mobility levels of elderly people in their natural environment. Mobility is measured by an accelerometer-based portable unit, worn by each monitored subject. Mobility level summaries are transmitted hourly, as an SMS message, directly from the portable unit to a remote server for long-term analysis. Each subject's mobility levels are monitored using custom-designed mobility alert software, and the appropriate medical personnel are alerted by SMS if the subject's mobility levels decrease